2014
DOI: 10.5901/mjss.2014.v5n23p158
|View full text |Cite
|
Sign up to set email alerts
|

Market Orientation and Firm Performance among Nigerian SMEs: The Moderating Role of Business Environment

Abstract: The purpose of this study is to examine the relationship between market orientation and firm performance, with the moderating variable of business environment. The study employed a cross sectional research design, using a structured questionnaire survey with a sample of 640 SMEs fully operational in Kano state, a total of 511 valid questionnaires were completed and returned representing 79.8 percent response rate. The finding from the study shows that the relationship between market orientation and firm perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 36 publications
2
18
0
1
Order By: Relevance
“…Regrettably, MO has resulted insignificant both directly and indirectly by inclusion of mediation. Though, the insignificant result of market orientation concurred with past literature (Han et al, 1998;Shehu & Mahmood, 2014).…”
Section: Discussionsupporting
confidence: 75%
“…Regrettably, MO has resulted insignificant both directly and indirectly by inclusion of mediation. Though, the insignificant result of market orientation concurred with past literature (Han et al, 1998;Shehu & Mahmood, 2014).…”
Section: Discussionsupporting
confidence: 75%
“…A review of the literature on customer satisfaction reveals several antecedents of customer satisfaction. Researchers claim that market orientation and business performance are intrinsically related through the essential factor of customer satisfaction: as the customer satisfaction is considered as the heart of marketing concept (Patterson, Johnson and Spreng 1996), meanwhile Researchers (Shehu and Mahmood 2014;Reza Jalali et al 2013;Grönroos 1995), proposed that organization need to satisfy customers in order to develop a long-term relationship.…”
Section: Customer-defined Market Orientation and Customer Satisfactionmentioning
confidence: 99%
“…(Buli, 2017) also found that MO was an important factor for SME performance. However, (Shehu and Mahmood, 2014) failed to find a direct relationship between MO and SME performance. Another opinion from (Njeru and Kibera, 2016) states that market orientation (MO) has been recognized by scholars and practitioners as the main key related to thinking about modern marketing methods, and one of the determinants of superior company performance, and a key source of competitive advantage.…”
Section: Market Orientation and Sme Performancementioning
confidence: 89%
“…The results of the study prove that MO has a positive effect on the performance of SMEs (Lekmat et al, 2018;Protcko and Dornberger, 2014). Other studies prove no effect (Buli, 2017;Shehu and Mahmood, 2014).…”
Section: Introductionmentioning
confidence: 91%